Not an infection: Endogenous circoviral elements underlie BFDV detections in Old World vultures - Iñigo Palacios-Martínez; Francisco Morinha; Guillermo Blanco (PLoS ONE, 2026)
Circoviruses (family Circoviridae) are small, single-stranded DNA viruses known to infect a broad range of bird species. The Beak and Feather Disease Virus (BFDV), typically associated with parrots, has occasionally been reported in unrelated avian taxa, raising questions about host range and potential spillover. We investigated BFDV-like sequences in three sympatric vultures breeding in Spain (Egyptian vulture Neophron percnopterus , cinereous vulture Aegypius monachus , and griffon vulture Gyps fulvus ). PCR screening revealed low and inconsistent prevalence in Egyptian vultures (7.4%, n = 163) and cinereous vultures (2.9%, n = 47), and absent in griffon vultures (n = 35). Phylogenetic analyses identified nine highly divergent haplotypes spanning three distinct clades, with no structure by species, geography, or year, and no evidence of nest- or territory-level transmission. These patterns contradict expectations for an actively circulating virus and instead suggest that the sequences represent endogenous circoviral elements (ECV) integrated into the host genome. The absence of clinical signs, except in one inbred Egyptian vulture nestling (offspring of a brother-sister mating), indicates these elements are non-pathogenic. Our findings demonstrate that BFDV detections in non-psittacine birds often reflect genomic remnants rather than active infections. This reinterpretation underscores the need to combine molecular surveillance and evolutionary genomics to distinguish actual infections from viral relics.